Ideational Meanings Associated to the Gay Community in Texts from the Chilean Cyber Press [Significados Ideacionales Asociados a la Comunidad Gay en Textos de Ciberprensa Chilena] - Araya-Seguel, C (Universidad de la Serena,Departamento de Artes y Letras, 2020)
This article describes the participation of social actors from the gay community in the Chilean cyber press between 2012-2017. These texts were gathered in the socio-historical context of significant milestones for the gay community: the Zamudio Case, Anti-discrimination Law, Civil Union Agreement and discussion on Equal Marriage. The participation of these social actors is explored using the IDEATIONAL system from functional systemic linguistics (FSL). The processes associated with the collective and individual actors that represent the gay community in the corpus shape socio-cultural phenomena linked to the political work and influence of these actors in social changes. The social role of the gay community evidences realignments of power relations which can be synthesized in the ideological category “political gay” and its variants, “victim” and “activist”. © Este trabajo se encuentra bajo la licencia Creative Commons Attribution 3.0.